Pediatric acute lymphoblastic leukemia relapse and prognosis: key predictors and therapeutic implications - Chen, XiaoYan; Wu, LingLing; Kuang, CaiYun; Wang, JiaYi; Hao, WenGe; Jiang, Hua; Zhang, WeiNa (Frontiers in Pediatrics, 2025)
BackgroundPediatric acute lymphoblastic leukemia (ALL), the most common childhood malignancy, achieves >95% 5-year survival with risk-adapted therapies. Nonetheless, 10%–15% of patients experience relapse, with post-relapse survival <50%. Challenges remain in optimizing minimal residual disease (MRD)-guided strategies and salvage therapies in ALL.AimsThis study aimed to identify relapse predictors and assess post-relapse outcomes among 436 pediatric ALL patients treated according to the CCCG-ALL-2015 protocol.ResultsOf the 436 enrolled patients (median age: 3.9 years; 92.4% B-ALL), sixty-four patients (14.7%) relapsed, predominantly with isolated bone marrow involvement (71.9%). Independent predictors included thrombocytopenia at diagnosis (OR = 2.09, P = 0.037), BCR::ABL1(+) (OR = 3.85, P = 0.024), and positive MRD on day 19 (OR = 2.09) and day 46 (OR = 5.73, P < 0.001) of induction therapy. Post-relapse, isolated extramedullary cases showed higher OS (100% vs. 72.9%, P = 0.078) than bone marrow relapses. HSCT significantly improved OS in bone marrow relapse comparing to patients treated with chemotherapy or CAR-T alone (82.6% vs. 38.1%, P = 0.027).ConclusionThrombocytopenia at diagnosis, BCR::ABL1(+), and persistent MRD are critical relapse predictors. HSCT remains pivotal for bone marrow relapse. Incorporating platelet counts into risk stratification and optimizing MRD-guided bridging therapies may enhance outcome. Future research should prioritize thrombocytopenia mechanisms and HSCT preconditioning strategies.